Policy without politicians bureaucratic influence in comparative perspective - Page, Edward (Oxford Oxford University Press, 2012)
A comparative study of the everday policy-making role of bureaucrats in six jurisdictions: France, US, Germany, Sweden the EU, and the UK. It takes as its central focus the decrees and regulations that account for a large proportion of government activity and explores the role of civil servants in their production.
Includes bibliographical references and index.
Keywords: Political planning; Political planning -- Case studies; Bureaucracy; Civil service